Effects of NAMPT polymorphisms and haplotypes on circulating visfatin/NAMPT levels in hypertensive disorders of pregnancy - Luizon, Marcelo R.; Belo, Vanessa A.; Palei, Ana C. T.; Amaral, Lorena M.; Lacchini, Riccardo; Sandrim, Valeria C. [UNESP]; Duarte, Geraldo; Cavalli, Ricardo C.; Tanus-Santos, José E. (Nature Publishing Group, 2015)
Dysregulation of adipocytokines may be associated with endothelial dysfunction in women with preeclampsia (PE), who are at increased risk of future cardiovascular disease. Visfatin, an adipocytokine with a potential cardiovascular role, is also known as nicotinamide phosphorybosil transferase (NAMPT). NAMPT gene polymorphisms affect circulating visfatin/NAMPT levels in obesity. Most findings provide evidence for increased visfatin/NAMPT circulating levels in PE. However, no previous study has tested the hypothesis that NAMPT polymorphisms affect visfatin/ NAMPT levels in hypertensive disorders of pregnancy. We studied the effects of the NAMPT polymorphisms T > C (rs1319501) and A > G (rs3801266), and the haplotypes formed by them on visfatin/NAMPT levels and whether these genetic markers are associated with gestational hypertension (GH) and PE. We studied 212 healthy pregnant (HP), 181 patients with GH and 208 with PE. Genotypes were determined by Taqman allele discrimination assays. Plasma visfatin/ NAMPT levels were measured by ELISA. No significant differences in visfatin/NAMPT levels were found among the groups. However, higher visfatin/NAMPT levels (P<0.05) were found in GH patients carrying the AG or the GG genotypes for the rs3801266 polymorphism or the 'T, G'haplotype. The TC and CC genotypes and the C allele for the rs1319501 polymorphism were more frequent in the HP than in the PE group (P<0.05). Moreover, the 'C, A'haplotype was also more frequent in the HP than in the PE group (P<0.01). Our findings suggest that although the rs3801266 polymorphism and the 'T, G'haplotype affect visfatin/ NAMPT levels in GH, the rs1319501 polymorphism and the 'C, A'haplotype affect the susceptibility to PE.
Keywords: Adipocytokine; Gestational hypertension; Haplotypes; NAMPT; Preeclampsia; Visfatin